KEADAAN INSOLVENT PADA PERUSAHAAN YANG MENGALAMI KEPAILITAN TERKAIT KEWAJIBAN MEMBAYAR UPAH (STUDI UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA) - Jesica Alfani Chrisisn (2022)
The bankruptcy decision is a consequence of the debtor's non-payment of his financial obligations for overdue debts. Whether the debtor has met the conditions for bankruptcy is what the judge considers when issuing the bankruptcy order, whether the debtor is solvent (able) or insolvent (unable to pay). The debtor's incapacity must be accompanied by specific action, either voluntarily by the debtor himself or at the request of a third party. Bankruptcy has a purpose, viz. to distribute the assets of the debtor to the creditors by the trustee. Employees who are preferred creditors have the privilege of paying wages in advance. The question of wages is very interesting to discuss because there are different perceptions and interests regarding wages because there is the job creation law and its derivatives that regulate that there are opinions on the question of bankruptcy in the link with the payment of workers to gives salaries